2005
DOI: 10.1002/ajh.20446
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative management of a patient with May-Hegglin anomaly requiring craniotomy

Abstract: May-Hegglin anomaly (MHA) is a rare type of autosomal dominant platelet disorder associated with mutations in the gene encoding nonmuscle myosin heavy chain 9 (MYH9). It is characterized by the presence of large platelets, leukocyte inclusions, and thrombocytopenia. The bleeding tendency is usually mild, but severe hemorrhages have been reported. This is the first reported case of a patient with MHA who underwent craniotomy for intractable seizure disorder of temporal lobe origin. Patients who have thrombocyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…Though it is rare for a MHA patient to develop severe bleeding intraand post operatively, the skilled foot and ankle surgeon should be aware of the risk of bleeding requiring transfusions. 5 Desmopressin acetate (DDAVP), is a synthetic vasopressin analogue that has been used perioperatively in patients with MHA. It is an altered form of vasopressin in which deamination of hemicysteine at position 1 and substitution of Darginine for L-arginine at position 8 has occurred.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Though it is rare for a MHA patient to develop severe bleeding intraand post operatively, the skilled foot and ankle surgeon should be aware of the risk of bleeding requiring transfusions. 5 Desmopressin acetate (DDAVP), is a synthetic vasopressin analogue that has been used perioperatively in patients with MHA. It is an altered form of vasopressin in which deamination of hemicysteine at position 1 and substitution of Darginine for L-arginine at position 8 has occurred.…”
Section: Discussionmentioning
confidence: 99%
“…5 Sehbai, et al, reported a case where 34-year old woman with known MHA underwent a craniotomy secondary to an intractable seizure disorder since childhood. 5 After an extensive family history, past medical history of the patient, and extensive workup which included; magnetic resonance imaging (MRI) of the brain, positron emission tomography (PET) scan, and 24 hour video EEG, the woman underwent craniotomy and resection of the temporal lobe foci of seizure activity. She was admitted one day prior to surgery and transfused with 6 units of platelets, and one hour before surgery was given DDAVP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5,10] Thrombocytopenia in these patients usually does not respond to treatment with corticosteroid or splenectomy. [11,12] Reduction of GP1b/IX/V in large platelets may contribute to bleeding diathesis, but the risk of bleeding is not high. [13] Renal involvement typically presents with variable degrees of proteinuria or microscopic hematuria in young individuals, although patients can also present with severe renal impairment and histological findings of global glomerulosclerosis, interstitial fibrosis, and marked tubular atrophy.…”
Section: Dyh Yap Et Almentioning
confidence: 99%
“…A genetic International Journal of Hematology Research neutrophil and monocytes [2] . Clinical manifestations of MHA vary from mild to severe bleeding, but the latter tends to be unusual [3] . A rare disorder, it is often misdiagnosed and can lead to inappropriate administration of drugs.…”
Section: Introductionmentioning
confidence: 99%